2010
DOI: 10.1504/writr.2010.031585
|View full text |Cite
|
Sign up to set email alerts
|

Port risk management and Public Private Partnerships: factors relating to risk allocation and risk sustainability

Abstract: Ports are complex operations involving government and private-sector partners in creating economic benefits and in identifying, managing and absorbing economic, environmental and security risks. Allocation and assessment of risks is necessitated and facilitated by the diversity of organisations involved. Allocation of the cost of risks among the partners or its transfer to outside agencies through insurance or financing arrangements is essential. However, this allocation is not purely a function of attributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…All activities are potentially disrupted since the activities are conducted by person. Stevedoring activities are already risky before the pandemic due to container weight failure and it may disrupts port schedule (Heikkila, 2018) and increasing the risk of safety incident (Schachler & Navare, 2010), as the pandemic started it is affected since there is a restrictions to reduce staff at work and both operations might be disrupted. Same thing applies to truck availability and warehouse activity (Alyami, 2014), due to the restrictions there were no truck drivers available and the goods are piled up in the warehouse.…”
Section: House Of Riskmentioning
confidence: 99%
“…All activities are potentially disrupted since the activities are conducted by person. Stevedoring activities are already risky before the pandemic due to container weight failure and it may disrupts port schedule (Heikkila, 2018) and increasing the risk of safety incident (Schachler & Navare, 2010), as the pandemic started it is affected since there is a restrictions to reduce staff at work and both operations might be disrupted. Same thing applies to truck availability and warehouse activity (Alyami, 2014), due to the restrictions there were no truck drivers available and the goods are piled up in the warehouse.…”
Section: House Of Riskmentioning
confidence: 99%
“…Villalba-Romero et al [22] indicated that the environmental perspective of sustainability shows great importance during the operation and maintenance stages. Combining the three levels, Schachler and Navare [23] used the reasonable governance framework and contract structure to achieve effective the identification and distribution of risks, further ensureing the sustainable development of PPP projects.…”
Section: Ppp Projects From the Sustainability Perspectivementioning
confidence: 99%